THE PROBLEM OF UNDERSTANDING ISLAMIC FAMILY LAW: BETWEEN NORMATIVE TEXTS, SOCIAL PRACTICES AND MODERN LEGAL DYNAMICS IN ISLAMIC FAMILY LAW UNDERGRADUATE STUDENTS IN MANDAILING NATAL - Yurizka Syahdani Nst; Sakinah Azzahra Hsb; Nur Asliah; Musa Azhari; Putra Halomoan Hsb; Purnama Hidayah Harahap (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Understanding Islamic family law is an important aspect in Islamic law education, especially for students of the Islamic Family Law Study Program. However, in practice, various problems are still found that originate from the dominance of the textual approach, the gap between classical fiqh and social reality, and the complex relationship between Islamic law and state law. This research aims to analyze the problems of understanding Islamic family law in S1 students of Islamic Family Law in Mandailing Natal by highlighting the tension between normative texts, social practices, and modern legal dynamics. This research uses a qualitative approach with a field study method (field study), through observation and analysis of empirical data associated with normative and sociological studies. The research results show that students' understanding of Islamic family law still tends to be normative-textual and not completely contextual. The maqaṣid al-syari'ah approach is offered as a methodological solution to bridge the gap, because it is able to integrate the purpose of Islamic law with the demands of social justice and protection for vulnerable groups. This research emphasizes the importance of updating the Islamic family law education approach to be more responsive to social development and modern law.